Recovery of rare earth elements from coal fly ash using enrichment by sodium hydroxide leaching and dissolution by hydrochloric acid. Issue 1 (4th March 2022) - Trinh, Ha Bich; Kim, Seunghyun; Lee, Jaeryeong
ABSTRACT: The most common method to recover valuable rare earth elements from the potential resource coal fly ash is direct leaching in acidic solution. However, the extraction of rare earth elements using only acid leaching is not sufficiently effective due to the presence of Al-Si-based glasses. In the present work, pre-treatment using NaOH leaching was investigated to reduce the content of Al-Si-based phase before subjecting to acid leaching. The treatment at conditions NaOH 5 M, at 100 °C and for 120 min could dissolve 53% of the ash sample, and the rare earth contents were enriched from 267 mg/kg to 556 mg/kg. The NaOH leaching promote the further extraction of rare earth elements in all of acid medias (HCl, HNO3 and H2 SO4 ), and HCl was the most effective leachant. More than 90% of rare earth elements was dissolved in 5 M HCl solution at 50°C after 120 min. The combination of NaOH treatment and HCl leaching presented an effective approach to extract rare earth elements from coal fly ash with enrichment of rare earth element contents, increase the leaching efficiency and avoidance of harmful impacts to the environment due to the conventional pre-treatment using alkaline roasting.